L. Frank Baum's The Wizard of Oz - Powell, Martin; Baum, L Frank; Break, Jorge (Minneapolis, Minn Stone Arch Books, 2010)
Dorothy and her dog, Toto, are carried away by a cyclone and crash down in a strange land called Oz, where they learn that to return home, Dorothy must travel to the Emerald City and meet the all-powerful Wizard of Oz. Includes notes abut the orignal story, glossary, discussion questions, and writing prompts
A gift from book Africa
Comic Strips
1 2 13
NEW_ZTN_GN
Keywords: Graphic novels; Oz (Imaginary place) -- Comic books, strips, etc